A study of gestational diabetes mellitus and fetal outcome in a tertiary care center - Mashkaria, Aashka M.; Patel, Babulal S.; Mashkaria, Aastha M.; Shah, Akshay C.; Jani, Shashwat K.; Patel, Adwait B.; Mehta, Raj M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Modern desk-bound lifestyle and unhealthy dietary changes have brought a rise in the prevalence of obesity and gestational diabetes mellitus (GDM). It is associated with severe hazards to the mother and the baby. It is mandatory that early diagnosis ensues and timely and congruous management is undertaken. Methods: In this observational study, 1250 women were included. A standardized questionnaire was formed and their details were noted. Tests for glucose levels, complete blood picture, urine examination were performed. An oral glucose tolerance test was performed on all the patients. Neonatal outcomes in terms of birth weight and the presence of complications were noted. Results: A total 201 (16.1%) of all women were having gestational diabetes mellitus (GDM). Most mothers were in the 25-30 age group. The majority of the women had a BMI between 26-30. 21.9% of babies were having weight >3.5 kgs. 11.4% of babies were <2.5 kgs. Out of 201 neonates, 90 babies were having complications. Major complications in neonates were macrosomia and respiratory distress. Therefore, early diagnosis, glycemic control, and timely and congruous management are advantageous to both mother and baby. Conclusions: GDM complicating the pregnancy results in a higher prevalence of complications in the mother and the neonate. Therefore, appropriate control of the sugar level in mothers is necessary and it decreases the morbidity and mortality rates in the babies as well as the mothers.